Inaktivasi Termal Spora Bacillus Subtilis Dalam Jus Nanas - Khaira Khaira; Evelyn Evelyn; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bacillus subtilis is a spore-forming bacterium and has been identified as spoilage in fruit-based medium such as pineapple. Food preservation by thermal processing is a conventional method and is still used today. The purpose of this study was to determine the effect of temperature (T: 90 °C, 95 °C, 100 °C) and pH(2 and 6) on the thermal inactivation of B. subtilis spores. It was shown that higher temperature resulted in the decreasing of the time needed to inactivate the spores. Higher resistance of the spores were observed at higher pH. The D-values obtained at pH 2 and temperatures of 90, 95, 100 °C were 11,24; 5,85, and 2.34 minutes, respectively. D-values at pH 6 were; 38,46, 13,70 and 3,55 minutes. The z-values obtained were in the range 9-14 °C. The results of this study indicate the importance of temperature and pH for heat resistance of B. subtilis spores in pineapple juice. Keywords: Bacillus subtilis, Inactivation, Pineapple juice, Resistance, Spores